Tendências espectrais de explosões solares em frequências Sub-THz - Fernandes, Luís Olavo de Toledo (2017)
Previous sub-THz studies were derived from single event observations. Spectral trends for a larger collection of sub-THz bursts have been analyzed for the first time. It consists of a set of 16 moderate to small impulsive solar radio bursts observed at 0.2 and 0.4 THz by the Solar Submillimeter-wave Telescope (SST) between 2012 and 2014 at El Leoncito, in the Argentinean Andes.The peak burst spectra included data from new solar patrol radio telescopes (45 and 90 GHz),and were complemented with microwave data obtained by the RSTN, when available. We evaluate critically errors and uncertainties in sub- THz flux estimates caused by calibration techniques and the corrections for atmospheric transmission, and introduce a new method to obtain uniform flux scale criterion for all 16 events. The sub-THz bursts were searched during reported GOES soft x-ray events of class C or larger, during periods of the SST observations. Seven out of 16 events exhibit spectral maxima in the range 5-40 GHz with fluxes decaying at sub-THz frequencies (3 of them associated to GOES class X, and 4 to class M). Nine out of 16 events exhibited the sub-THz spectral component. From these, 5 events exhibited the sub-THz emission fluxes increasing with frequency separated from the microwave spectral component (2 classified as X and 3 as M) and 4 events have been detected at sub-THz frequencies only (3 classified as M and 1 as C). The results suggest that the THz component might be always present, with the minimum turn-over frequency increasing as a function of the energy of the emitting electrons. In view of the peculiar nature of many sub-THz bursts events, their better understanding requires further investigations of bursts examined on the standpoint of SST observations alone.